Guest editors’ introduction: special issue on Inductive Logic Programming and on Multi-Relational Learning - Zaverucha, Gerson; Vítor, Santos Costa (Machine learning, 2015)
Issue Title: Special Issue on Inductive Logic Programming and on Multi-Relational Learning; Guest Editors: Gerson Zaverucha and Vitor Santos Costa